2016
DOI: 10.1093/femsle/fnw028
|View full text |Cite
|
Sign up to set email alerts
|

Rumen ciliate protozoa of domestic sheep (Ovis aries) and goat (Capra aegagrus hircus) in Kyrgyzstan

Abstract: Species composition and concentration of rumen ciliate protozoa were investigated in the rumen contents of 14 domestic sheep and 1 goat living in Bishkek, Kyrgyzstan. This is the first report on rumen ciliates from ruminants living in Kyrgyzstan. In sheep 12 genera, 28 species and 12 morphotypes were detected, whereas in goat 8 genera, 12 species and 4 morphotypes were detected. The density of ciliates in sheep was (28.1 ± 20.0) × 10(4) cells mL(-1) and in goat was 37.0 × 10(4) cells mL(-1). Dasytricha ruminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…A study in cattle indicated that Entodinium, Diplodinium, Eremoplastron, Ostracodinium, Eodinium, Epidinium, Isotricha, and Dasytricha were among the most abundant genera (> 1%) of a total of 13 identified in the ruminal fluid by microscopic identification and counting [38]. Conversely, in sheep and goats, 12 and 8 genera were identified, being Dasytricha, Entodinium, Eudiplodinum, Diplodinium, Isotricha, and Metadinium the more abundant (> 1%) in both species, and Enoploplastron, Ophryoscolex, and Polyplastron only in sheep [39].…”
Section: Protozoamentioning
confidence: 94%
“…A study in cattle indicated that Entodinium, Diplodinium, Eremoplastron, Ostracodinium, Eodinium, Epidinium, Isotricha, and Dasytricha were among the most abundant genera (> 1%) of a total of 13 identified in the ruminal fluid by microscopic identification and counting [38]. Conversely, in sheep and goats, 12 and 8 genera were identified, being Dasytricha, Entodinium, Eudiplodinum, Diplodinium, Isotricha, and Metadinium the more abundant (> 1%) in both species, and Enoploplastron, Ophryoscolex, and Polyplastron only in sheep [39].…”
Section: Protozoamentioning
confidence: 94%
“…The number of ciliate genera in sheep living in İzmir, Turkey was higher than that in sheep from Canada (Imai et al 1989), Egypt (Selim et al 1996), Libya (Selim et al 1999), Northern Cyprus (Göçmen et al 2001;Göçmen & Gürelli 2009a, b), and Egypt (Baraka 2012), but less than sheep from Turkey (Göçmen et al 1999;Öktem et al 1997) and Kyrgyzstan (Gürelli et al 2016). However the number of ciliate species in sheep living in İzmir, Turkey was less than that in sheep from Turkey (Göçmen et al 1999;Öktem et al 1997), Northern Cyprus (Göçmen et al 2001;Göçmen & Gürelli 2009a, b), and Kyrgyzstan (Gürelli et al 2016) and higher than sheep from Canada (Imai et al 1989), Egypt (Selim et al 1996), Libya (Selim et al 1999), and Egypt (Baraka 2012) (Table 3). Although the sheep were from the same area (İzmir) of Turkey in this study and other studies (Göçmen et al 1999;Öktem et al 1997) and the number of sheep studied increased in this study, the number of ciliate species decreased.…”
Section: Discussionmentioning
confidence: 91%
“…Ciliate densities were calculated at 400× magnification with a Neubauer hemocytometer counting chamber. Differential counts of species were estimated from smear slides with 75-1500 cells of each species (Gürelli et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Of the rumen microorganisms, bacteria are the most abundant with concentrations 10 5 times higher than fungi or protozoa (de Almeida et al, 2012;Gürelli et al, 2016;Rira et al, 2016). The various types of rumen bacteria work together to ferment the various plant substrates into energy compounds utilised by the host for growth and development.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Though the rumen has substantial fungi and protozoan populations, they are far fewer than the prokaryotic community. Rumen fungi have been found in the rumen at concentrations of 1.6 to 8.8 x 10 5 cfu mL -1 (de Almeida et al, 2012), with rumen protozoa at a similar concentration of 8.1 x 10 4 to 4.8 x 10 5 cells mL -1 (Gürelli et al, 2016). As rumen bacteria are far more numerous, with concentrations of 1 x 10 11 cells g -1 (Hungate, 1966;Rira et al, 2016), they are more likely to have the greatest impact on digestion.…”
Section: Introductionmentioning
confidence: 98%